Acute intermittent porphyria – A case report - Veljović, Milić; Vulović, Tatjana; Ristanović, Aleksandra; Vuković, Rade (Vojnosanitetski pregled, 2021)
Introduction. Acute intermittent porphyria is a rare inherited metabolic disorder caused by a decreased level of porphobilinogen deaminase. Subsequent accumulation of byproducts in neural elements causes a classic triad of abdominal pain, neurological dysfunction, and psychiatric disturbances. Case report. A 22-year-old female patient with convulsions, episodes of blindness and progressive development of quadriparesis, bulbar paralysis, and respiratory failure was admitted to our intensive care unit twelve days after undergoing colon resection at the local hospital. The diagnosis was confirmed by a high level of porphobilinogen in urine. Previous use of oral contraceptives, antidepressants, and thiopental as induction agents for general anesthesia could represent precipitating factors. The patient was treated conservatively with high carbohydrate intake and human hemin. Six months after admission, the patient was transferred to the Department of Physical Medicine and Rehabilitation. Conclusion. Early diagnosis of acute intermittent porphyria is the cornerstone for successful treatment. The next step includes adequate therapy followed by the prevention of attacks.